Helmet design requirements for shared micromobility Overview and Design Guidelines - Mingote, Miguel (2023)
Micromobility is a very current topic, particularly in city centres of developed countries, powered by the introduction of shared electric scooters. But along with the benefits came the problems associated to the lack of laws, adequate infrastructures, and protective devices. With the number of accidents rapidly growing, and injuries to the head and face being commonly found with e-scooter hospital admissions. There is evidence that craniofacial trauma could be significantly reduced by wearing a protective helmet. Some measures like mandatory helmet legislation and the offer of folding helmets on the market have been developed to tackle this issue but are focused on the purpose of individual use. The challenge of this investigation is to appeal to shared micromobility services such as e-scooters and e-bikes, by providing a protective device, like a helmet, suited to the specific needs of micromobility users, by being able to adapt to the spontaneous nature of this means of transportation and encourage users to start riding safely. Strategically, this project is intended to contribute to the adoption of safe riding habits, through the development of a product in the domain of engineering and product design, structured by the patterns of ecoefficiency, the usage of sustainable materials and low impact manufacturing processes, lifecycle assessment and reduced maintenance, in order to go along with the premises that involve this type of transportation and with the sustainable development strategies included in the United Nations 2030 Agenda.